Tsunami Surveillance By Satellites. - Digregorio, B.E (IEEE spectrum)
A group of scientists claim to have developed a concept for a tsunami warning system that relies on Global Positioning System (GPS) with the ability to detect these deadly waves in as little as 15 minutes. The system works by measuring GPS satellite radio signals as they are picked up during an undersea earthquake by GPS ground stations positioned around the globe. Data from the GPS ground stations can be used to gauge the precise strength of the earthquake, and that in turn would help predict the size of a resulting tsunami